Toward the Role of Teacher Empathy in Students’ Engagement in English Language Classes - Zhang, Zhichao (Frontiers in Psychology, 2022)
This paper aimed at examining the related studies on the relationship between teacher empathy and learner engagement in English as a Foreign Language (EFL) learning contexts. The positive and significant relationship between teacher empathy and learner engagement has been verified in the literature. Studies have shown the positive influence of teacher-learner rapport on learner engagement. Moreover, studies indicated that teacher empathy leads to learner self-confidence in educational contexts. The literature review has also shown that teachers’ provision of a positive environment through empathy, sympathy, and kindness can trigger learner motivation and engagement. Moreover, teachers’ empathy can reduce the stress level which, in turn, positively affects learners’ engagement level. Eventually, the pedagogical implications to engage learners and teachers in academic contexts have been provided. However, some suggestions have been offered to expand the insights over the associations between positive psychological constructs and teachers’ emotions.